An Iterative Power Gradient Searching Algorithm Toward the Slot and Power Joint Scheduling Problem in MANET Broadcast - Xu Zhao; Zuyao Ni; Hanyu Tian (IEEE Access, 2025)
Broadcast is a fundamental network service in mobile ad hoc networks (MANETs). Despite a plethora of research on ad hoc networks’ broadcast, there has been minimal research on slot and power joint scheduling. In this study, we focused our investigation on slot and power joint broadcast scheduling to maximize the throughput under a dynamic topology with a minimum delay and energy. Due to the difficulty of multi-target optimization in the dynamic topology, we decoupled the problem into two subproblems iterating with each other: minimum-delay slot scheduling and maximum-throughput minimum-energy power gradient searching, both of which process the primary topology considering the mobility of the nodes, thus forming the algorithm Iterative Power Gradient Searching. In the power gradient searching, we exploited the Monte Carlo Tree Search by utilizing the hierarchical nature of multihop transmission to reduce complexity. Through theoretical proof and extensive simulations, we demonstrated that Iterative Power Gradient Searching achieved a maximum throughput in the dynamic topology with a minimum delay and energy approximately.